The Lexicon of Lukašenka’s Authoritarianism and the Russo-Ukrainian War: The Case of Belarusian Language - Ivanoŭ, Uladzislaŭ (Populismo y propaganda: entre el presente y el pasado, 2020)
The subject of this article is the use of language in the midst of the conflict between Russia and Ukraine, and also the language of authoritarianism as a resource of the official propaganda of the Lukašenka regime. The central theme is the Belarusian language and how it is used to portray the strife (a simple conflict or crisis according to the regime and a war according to the opposition) outside the country, how it describes and transmits the ideological orientation of the different political forces, how official agents (authorities) and unofficial agents (the opposition) influence the language and finally how native speakers react to the situation by forging new words, by criticizing and sometimes by making fun of the language usage. The use of the Belarusian language during this time of conflict is examined through the prism of national stereotypes, which, in radical conditions, turn into hate speech and can lead to war. With this, the research tackles an unexpected dimension: under the influence of the activity of radical Russian groups nicknamed “the Russian world”, the Belarusian language has become the object of attacks, of criticisms, a real victim of propaganda and war.